Psychological features of personality preparation to professional activity. (The Journal of Psychology and Sociology, 2012)
In the article the problem of preparedness of students to professional activity and methods are examined educating in an educational process, that provide preparedness. Research of this theme in present time did not lose the actuality. The problem of preparation of the future specialists, forming for them is a personality, professional competence very important. Also, basic treat results that were got during experimental work are given in the article. As charts data are shown at forming of components of competence, also, communicative competence of specialists and loud speaker development of forming of professional competence at a control group and students (before and after an experiment).
Keywords: professional preparatin; competence; communicativenes; self-development; image of preparation; pedagogical abilities; methods of mutual action; self-determination.